INDUSTRI TPT INDONESIA DALAM ACFTA : Siapa Juragan di Pasar Domestik? - Rahman, Agus Rubianto (Pusat Penelitian Politik, 2011)
AbstractACFTA was in force since January 2010 in six ASEAN countries and otherfour ASEAN countries in 2015Implementation of thefree trade area between China and ASEAN countries is possible and becomes political andeconomic reality It is historical achievement in their relations in which prior to their relations are colored bytremendous crisis As free trade regions ACFTA banding almost 1 9 billion peoples represented as the biggestfree trade area in the world From the beginning ACFTA is further revitalization of AFTA that ASEAN countriesprefer to be integrated by external actor in which China is more acceptable than Japan or South Korea ACFTA will show opportunities andproblems for all economic actors around the region especially for Indonesia te aileand textile product This makes Indonesian market as second market after China s market Indonesia still does notgive the high priority in export yet towardACFT4 but its percentage consistently tended to increased For importIndonesia also increased thisfrom ACFTA countries Based on this national grasp Indonesian textiles and textileproducts industry arefacing difficult periods especially expansion of China textile and textile product into hxlonesian domestic market Fortunately Indonesian textile and textile products have received the world heritage inwhich this emerged as new energyfor revitalization ofIndonesia textile and textile products in strengthening their competitive advantage and market shares in both domestic and international market Now and then Batik starts tobe the most outstanding Indonesian icon